Pembinaan Transformatif Bagi Warga Binaan Di Lembaga Pembinaan Anak Kelas II Batam - Fredy Simanjuntak; Rita Evimalinda; Ardianto Lahagu; Efvi Noyita; Ester Lina Situmorang; Agiana Her Visnhu Ditakristi (Sekolah Tinggi Teologi Real Batam, 2019)
This Mental and Spiritual Development Program was initiated by STT REAL Batam and GBI Windsor House of Glory. This coaching program is a routine program of STT REAL Batam to carry out the tridharma of higher education which is the first program or pilot project in collaboration with GBI Windsor Square House of Glory which is committed to the field of Mental and Spiritual Development of Christian Prisoners at the Batam Class II Child Development Institute. It is hoped that this coaching program can support government programs in rehabilitative, corrective, and educative services to inmates and participate in building life values so that they can equip inmates spiritually so that they can carry out their roles well. and good citizens. useful. This coaching program is a mentoring movement to improve the quality of piety to God Almighty, intellectual, professional attitudes and behavior, physical and spiritual health of the inmates. Furthermore, it is expected that they will be able to improve themselves and not repeat the crimes that have been committed.AbstrakProgram Mental dan Spiritual Development ini digagas oleh STT REAL Batam dan GBI Windsor House of Glory. Program pembinaan ini merupakan program rutin STT REAL Batam untuk mengemban tridharma perguruan tinggi yang merupakan program atau pilot project pertama bekerjasama dengan GBI Windsor Square House of Glory yang berkomitmen pada bidang Pembinaan Mental dan Spiritual Narapidana Kristen di Lembaga Pembinaan Anak Kelas II Batam. Diharapkan program pembinaan ini, dapat mendukung program pemerintah dalam pelayanan rehabilitatif, korektif, dan edukatif kepada warga binaan serta ikut membangun nilai-nilai kehidupan sehingga dapat membekali warga binaan secara spiritual agar dapat menjalankan perannya dengan baik. dan warga masyarakat yang baik. berguna. Program pembinaan ini sendiri merupakan gerakan pendampingan untuk meningkatkan kualitas ketakwaan kepada Tuhan Yang Maha Esa, intelektual, sikap dan perilaku profesional, kesehatan jasmani dan rohani warga binaan. Selanjutnya diharapkan pembinaan agar mereka mampu memperbaiki diri dan tidak mengulangi kejahatan yang telah dilakukan.